Auxins Released by Trichoderma atroviride Simultaneously Modulate Tomato Plant Growth and Root-knot Formation by Plant-parasitic Nematodes - Hexon Angel Contreras-Cornejo; Raúl Omar Real-Santillán; Pablo F. Jaramillo-López; John Larsen (Journal of Plant Growth Regulation, 2026)
Trichoderma includes several plant growth and health promoting species. However, information about combined plant growth modulation and biocontrol of plant parasitic nematodes is limited. In this work, the role of indole-3-acetic acid (IAA) produced by T. atroviride and released into the rhizosphere of tomato ( Lycopersicon esculentum L.) in regulating plant growth and its effects on soil nematodes with different lifestyles (i.e., bacterivorous, fungivorous, and plant-parasitic nematodes) were investigated. Experiments with and without T. atroviride in soil without and with plants were performed. In soil without plants, T. atroviride increased the total number of soil nematodes by 53%, though no significant effects were observed for the any of the ecological guilds. Also, the presence of the plant caused an 86% increase in the total nematode populations compared to the control treatment without plants. In nematode infested agricultural soil, T. atroviride increased the content of salicylic acid (SA) in plant roots. In addition, the levels of IAA, which controls practically all developmental processes in plants, were also increased, while pure IAA reduced gall formation in tomato roots. In soil without plants, T. atroviride released 591.10 ng g − 1 of IAA, corresponding to a 2-fold accumulation when compared with the levels found in non-inoculated soil. A positive correlation between the accumulation of IAA in the soil and SA in tomato roots was observed. In conclusion, our study revealed a possible new facet of the activity of IAA released by T. atroviride in the soil, modulating plant growth and reducing root gall formation during the process of plant-parasitic nematode infestation.

Long-Term Treatment with Alcaligenes faecalis A12C Improves Host Resistance to Pathogens in Septic Rats: Possible Contribution of Curdlan-Like Immune Trainer - C. J. Martel-Benítez; R. Alayón-Afonso; D. Padilla Castillo; F. J. Chamizo-López; M. Isabel García-Laorden; A. Espinosa de los Monteros y Zayas; J. C. Rivero-Vera; P. Nogueira Salgueiro; F. Real; A. Bordes-Benítez; A. Martel Quintana; C. Almeida Peña; et al. (Probiotics and Antimicrobial Proteins, 2025)
Curdlan, a β-1,3/1,6-glucan found in Alcaligenes faecalis ( A. faecalis ) wall, activates innate and humoral immunity. The aim of this study is to evaluate whether pretreated rats with A. faecalis A12C could prevent sepsis disturbances and identify the immunomodulatory mechanisms involved. Experiments occurred in two stages: a survival study with 16 rats randomly divided into septic (SC) ( n = 8) and septic pretreated (SA) ( n = 8) groups and 45 rats divided into four groups: healthy (AGUSAN) ( n = 9), septic (AGUIC) ( n = 13), septic pretreated (AGUIA) ( n = 14), and healthy pretreated (AGUSTO) ( n = 9). Sepsis was induced by cecal ligation and puncture after 30 days of A. faecalis A12C pretreatment or without. SA group had a higher survival rate of 58% vs. 16% for SC group ( P < 0.05). Overall, AGUIA showed better status than AGUIC ( P < 0.01). Higher monocytosis was found in AGUIA and AGUSTO vs. AGUIC and AGUSAN, respectively ( P < 0.05). A gradual increase in curdlan fecal concentration was observed in AGUIA during pretreatment. Fecal concentrations of Escherichia coli significantly decreased in AGUIA and AGUSTO. Bacterial load in urine, peritoneal lavage fluid (PLF), and bronchoalveolar lavage fluid (BALF) decreased ( P < 0.05) in AGUIA vs. AGUIC. Finally, lower inflammation was observed in serum, BALF, and PLF, with reduced IL-6, IL-10, IL-1β, and TNF-α, along with less damage in lungs and peritoneum in AGUIA vs. AGUIC. These findings suggest the connection between curdlan—produced by A. faecalis A12C—with the immune system and the reduction in severity of experimental sepsis.

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Promotion of tomato growth and suppression of plant parasitic nematodes by Trichoderma atroviride: alterations in root metabolomics and soil C/N ratio - Hexon Angel Contreras-Cornejo; Pablo F. Jaramillo-López; Raúl Omar Real-Santillán; John Larsen (Rhizosphere, 2025)

The neurotoxicity of pesticides: Implications for Parkinson's disease - Leslie Amaral; Márcia Martins; Manuela Côrte-Real; Tiago F. Outeiro; Susana R. Chaves; António Rego (Chemosphere, 2025)

Laboratory validation of a simplified model for estimating equilibrium PFAS mass leaching from unsaturated soils - John F. Stults; Charles E. Schaefer; Tamzen MacBeth; Yida Fang; Julie Devon; Isreq Real; Fangfei Liu; David Kosson; Jennifer L. Guelfo (Science of The Total Environment, 2025)

The Goldilocks Dilemma: the optimal management strategy for invasive trees in the Atlantic Forest - Rodolfo Cesar Real Abreu; Pablo J. F. P. Rodrigues (Biological Invasions, 2024)

A versatile yeast model identifies the pesticides cymoxanil and metalaxyl as risk factors for synucleinopathies - Leslie Amaral; Filipa Mendes; Manuela Côrte-Real; António Rego; Tiago F. Outeiro; Susana R. Chaves (Chemosphere, 2024)

Air-water interfacial collapse and rate-limited solid desorption control Perfluoroalkyl acid leaching from the vadose zone - John F. Stults; Charles E. Schaefer; Yida Fang; Julie Devon; Dung Nguyen; Isreq Real; Shilai Hao; Jennifer L. Guelfo (Journal of Contaminant Hydrology, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Impact of genetic diversity and antibiotic-resistance of Salmonella isolated from feral cats: One Health approach - C. Marin; M. Cerdà-Cuéllar; I. Rosario; L. Lorenzo-Rebenaque; S. Vega; A. Manzanares; D. Padilla; F. Real; E. Rodríguez-Ponce; B. Acosta-Hernández (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Probiotic Properties of Alcaligenes faecalis Isolated from Argyrosomus regius in Experimental Peritonitis (Rat Model) - A. I. Gutiérrez-Falcón; A. M. Ramos-Nuez; A. Espinosa de los Monteros y Zayas; D. F. Padilla Castillo; M. Isabel García-Laorden; F. J. Chamizo-López; F. Real Valcárcel; F. Artilles Campelo; A. Bordes Benítez; P. Nogueira Salgueiro; C. Domínguez Cabrera; J. C. Rivero-Vera; et al. (Probiotics and Antimicrobial Proteins, 2021)
A strain of Alcaligenes faecalis A12C ( A. faecalis A12C) isolated from Argyrosomus regius is a probiotic in fish. Previous experiments showed that A. faecalis A12C had inhibitory effects on the growth of multidrug-resistant bacteria. We aimed to confirm whether A. faecalis A12C is safe and has adequate intestinal colonization in experimental rats, and evaluate its efficacy in an animal model of peritonitis . We used 30 male rats, randomly divided into 6 groups ( n = 5): three groups (HA7, HA15, HA30) received A. faecalis A12C in drinking water (6 × 10 8 CFU/mL) for 7 days, and three control groups received drinking water only. All groups were evaluated at 7, 15, and 30 days. Survival after A. faecalis A12C administration was 100% in all groups. Mild eosinophilia (1.5%, p < 0.01) and increased aspartate aminotransferase (86 IU/L, p < 0.05) were observed in HA7, followed by progressive normalization. No histological signs of organ injury were found. We observed significant E. coli decline in faeces, parallel to an increase in A. faecalis A12C at 7 days. E. coli had a tendency to recover initial values, while A. faecalis A12C disappeared from the intestinal microbiota at 30 days. To evaluate its efficacy against peritonitis, we studied two additional groups of animals: IA group pretreated with A. faecalis A12C before E. coli intra-abdominal inoculation, and IC group inoculated with no A. faecalis A12C. We found an increase in C-reactive protein, alanine aminotransferase, urea, and eosinophils in IC animals when compared with IA. Peritonitis was more evident in IC than in IA animals. Our findings suggest that A. faecalis A12C altered clinically relevant parameters in sepsis and was associated with a lesser spread of infection.

Allegory of a cave crustacean: systematic and biogeographic reality of Halosbaena (Peracarida: Thermosbaenacea) sought with molecular data at multiple scales - Timothy J. Page; Jane M. Hughes; Kathryn M. Real; Mark I. Stevens; Rachael A. King; William F. Humphreys (Marine Biodiversity, 2018)

Human lactoferrin triggers a mitochondrial- and caspase-dependent regulated cell death in Saccharomyces cerevisiae - M. Acosta-Zaldívar; M. T. Andrés; A. Rego; C. S. Pereira; J. F. Fierro; M. Côrte-Real (Apoptosis, 2016)

Longitudinal evaluation of hepatitis C viral persistence in HIV-infected patients with spontaneous hepatitis C clearance - A. Rivero-Juarez; A. Caruz; L. M. Real; L. Martinez-Dueñas; F. J. Marquez; M. Frias; E. Recio; A. Gordon; J. A. Pineda; A. Rivero; A. Camacho (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

A porcine circovirus-2 mutant isolated in Brazil contains low-frequency substitutions in regions of immunoprotective epitopes in the capsid protein - Rafael Locatelli Salgado; Pedro Marcus Pereira Vidigal; Natalia F. Gonzaga; Luiz F. L. de Souza; Marcelo D. Polêto; Thiago Souza Onofre; Monique R. Eller; Carlos Eduardo Real Pereira; Juliana L. R. Fietto; Gustavo C. Bressan; Roberto M. C. Guedes; Márcia R. Almeida; et al. (Archives of Virology, 2015)

Impact of HIV infection on sustained virological response to treatment against hepatitis C virus with pegylated interferon plus ribavirin - P. Monje-Agudo; A. Castro-Iglesias; A. Rivero-Juárez; F. Martínez-Marcos; E. Ortega-González; L. M. Real; B. Pernas; N. Merchante; P. Cid; J. Macías; M. D. Merino; A. Rivero; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Assessment of hormone-like activities in Ginkgo biloba , Elettaria cardamomum and Plantago ovata extracts using in vitro receptor-specific bioassays - Macarena Real; José-Manuel Molina-Molina; Jesús Jimenez; Horacio R. Diéguez; Mariana F. Fernández; Nicolás Olea (Food Additives & Contaminants: Part A, 2015)

Elimination of Selected Emerging Contaminants by the Combination of Membrane Filtration and Chemical Oxidation Processes - Juan L. Acero; F. Javier Benitez; Francisco J. Real; Elena Rodriguez (Water, Air, & Soil Pollution, 2015)

Core amino acid variation at position 110 is associated with sustained virological response in Caucasian patients with chronic hepatitis C virus 1b infection - F. A. Di Lello; J. A. Mira; K. Neukam; M. Parra-Sánchez; J. R. Guelfo; C. Cifuentes; J. Macías; J. C. Palomares; J. Gómez-Mateos; J. A. Pineda; Luis M. Real (Archives of Virology, 2014)

Global diagnostic energetics of five state-of-the-art climate models - C. A. F. Marques; A. Rocha; J. Corte-Real (Climate Dynamics, 2011)

First report of Streptococcus iniae in red porgy ( Pagrus pagrus , L.) - F El Aamri; D Padilla; F Acosta; M J Caballero; J Roo; J Bravo; J Vivas; F Real (Journal of Fish Diseases, 2010)
This work describes the first isolation of Streptococcus iniae in red porgy, Pagrus pagrus (L.), and the first European isolation of this pathogen in gilthead seabream, Sparus aurata (L.). In both farmed fish species, infection resulted in lethargy, anorexia, abnormal swimming, exophthalmia and sudden death, with mortality rates of over 25% in red porgy and 10% in gilthead seabream. Beta‐haemolytic Gram‐positive cocci, catalase negative and oxidase negative, were isolated in pure culture from internal organs. Conventional and rapid identification systems, and 16S rRNA gene partial sequencing were used to identify the causative agent of the natural disease. LD 50 trials were carried out to show the virulence of this isolated strain in these species, with values of 1.7 × 10 4 CFU per fish in red porgy and 1.32 × 10 5 CFU per fish in gilthead seabream. The most prominent lesions were meningoencephalitis and multifocal infiltration of macrophage cells in the kidney and spleen.

Invasion and survival of Photobacterium damselae subsp. piscicida in non‐phagocytic cells of gilthead sea bream, Sparus aurata L. - F Acosta; J Vivas; D Padilla; J Vega; J Bravo; V Grasso; F Real (Journal of Fish Diseases, 2009)
Fluorescence microscopy and gentamicin protection assays were used to investigate the ability of four Photobacterium damselae subsp. pisicida (Phdp) strains to adhere to and to invade the fish epithelial cell line, SAF‐1, derived from Sparus aurata . All strains tested were detected intracellularly using both techniques, although internalization levels varied among strains. Treatment with cytochalasin D and experiments carried out at 4 °C demonstrated that a functional host cell cytoskeleton and active cell metabolism are necessary for bacterial internalization. Intracellular bacteria were detected for up to 7 days with a round morphology and were stained with DAPI, indicating that some bacterial cells may remain viable inside SAF‐1 cells. Our in vitro findings indicate that Phdp are capable of adhering, entering and surviving within the non‐phagocytic epithelial cell line SAF‐1, which may be important for persistence and establishment of a carrier state in S. aurata .

Temperature influences the expression of fimbriae and flagella in Hafnia alvei strains: an immunofluorescence study - D. Padilla; F. Acosta; J. A. García; F. Real; Jose R. Vivas (Archives of Microbiology, 2009)

Global atmospheric energetics from NCEP–Reanalysis 2 and ECMWF–ERA40 Reanalysis - Carlos A. F. Marques; Alfredo Rocha; João Corte‐Real; José M. Castanheira; Juan Ferreira; Paulo Melo‐Gonçalves (International Journal of Climatology, 2009)
The global atmospheric energy cycle is estimated on an annual basis using Reanalysis 2 data from the National Centers for Environmental Prediction and National Center for Atmospheric Research (NCEP/NCAR), and ERA 40 Reanalyses from the European Centre for Medium‐Range Weather Forecasts (ECMWF) for the period 1979–2001. A formalism to avoid belowground data on pressure levels intercepted by topography is adopted. No appreciable differences were found between the two datasets from the energetics point of view. The so‐called ωα and v ·grad z formulations were both used for the conversions from zonal available potential energy into zonal kinetic energy ( C Z ) and from eddy available potential energy into eddy kinetic energy ( C E ). Results with both formulations are comparable only when using the formalism preventing belowground data to enter into the computations. Atmospheric energetics are also computed using ECMWF Reanalyses for the period 1958–1978. A significant increase was found in the eddy kinetic and eddy available potential energies from the early period to the later period, likely related to the assimilation in the reanalyses of satellite data after 1979. The conversion rate, C Z , was found to change its sign throughout the years. The atmospheric energy cycle using the ECMWF Reanalyses data is compared with five previous estimates. Differences in the direction of the conversion rate, C Z , between the various estimates may be explained by the different time periods chosen for averaging. Owing to the omission of belowground data, the conversion from zonal available potential energy into eddy available potential energy ( C A ) was somewhat smaller in ECMWF Reanalyses than in the previous estimates. Despite those differences, an overall agreement may be found between the various estimates for the atmospheric energy cycle. Copyright © 2008 Royal Meteorological Society

Domain Formation in DODAB–Cholesterol Mixed Systems Monitored via Nile Red Anisotropy - Graham Hungerford; Elisabete M. S. Castanheira; Adelina L. F. Baptista; Paulo J. G. Coutinho; M. Elisabete C. D. Real Oliveira (Journal of Fluorescence, 2005)

Virulence factors and pathogenicity of Hafnia alvei for gilthead seabream, Sparus aurata L. - D Padilla; F Real; V Gómez; E Sierra; B Acosta; S Déniz; F Acosta (Journal of Fish Diseases, 2005)
Virulence factors ( eae gene, haemolytic capacity, fimbriae, resistance to the bactericidal effect of serum, siderophore production) and pathogenicity for gilthead seabream, Sparus aurata L., were analysed for 23 Hafnia alvei strains. None of the strains used in LD 50 studies were lethal for seabream at doses as high as >10 8 cfu mL −1 . In chronic challenge studies differences in severity of the inflammatory response were observed between strains. On the basis of correlation of the inflammatory response to different strains of H. alvei in seabream with those virulence factors studied, it was only possible to establish a positive correlation between pathogenicity and resistance to the bactericidal effect of fish serum. Gilthead seabream is thus a species with considerable resistance to experimental infection with H. alvei . The bacterium does, however, have the capacity to remain viable in seabream for up to 3 months, without any clinical signs. Hafnia alvei is a well‐recognized human and animal pathogen. Thus, as the pathogen can coexist with aquaculture operations, cultured gilthead seabream could represent a risk to human health as a carrier in some circumstances.

Hafnia alvei as an opportunistic pathogen causing mortality in brown trout, Salmo trutta L. - L. A. Rodríguez; C. S. Gallardo; F. Acosta; T. P. Nieto; B. Acosta; F. Real (Journal of Fish Diseases, 1998)
Strains of Hafnia alvei caused mortalities in brown trout , Salmo trutta L., following intraperitoneal injection with LD 50 values ranging between 1.3 × 10 4 and 2.5 × 10 7 bacteria fish −−1 . These values are considered to represent a high to moderate degree of virulence. Virulent strains were isolated from non‐fish sources. Fish surviving the LD 50 values continued to harbour the organism in the kidney, suggesting the establishment of a carrier state.

Chironomids and regional water types - Verdonschot; F. M. Piet; Montserrat Real; Joke A. Schot (Aquatic Ecology, 1992)